The Evaluation of The Minimum Service Standards Policy in The Health Sector at Jabon Community Health Center, Sidoarjo Regency, East Java - Lucky Fitvita Eka Brillyanti; Setya Haksama (Eduvest - Journal of Universal Studies, 2026)
The Minimum Service Standard (SPM) in the health sector is a government policy that aims to ensure the fulfillment of basic health services for the community. This study aims to evaluate the implementation of the Minimum Service Standard policy in the health sector at the Jabon Health Center, Sidoarjo Regency, East Java. This study uses a qualitative approach with a descriptive type of research. The research subjects consisted of the head of the Health Center, the person in charge of the SPM program, and the health workers who were selected purposively. Data collection techniques were carried out through in-depth interviews, observations, and document reviews. Data analysis was carried out qualitatively using an interactive model that included data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the SPM policy at the Jabon Health Center has generally been carried out in accordance with applicable regulations and supported by planning and implementation of services that refer to standard operating procedures. However, the achievement of SPM targets has not been fully optimal due to limited human resources, a high workload among officers, and low participation of some communities. Monitoring and evaluation were carried out, but they still tend to be oriented towards administrative fulfillment. This study concludes that the successful implementation of SPM in the health sector requires strengthening resource capacity, optimizing monitoring and evaluation functions, and increasing community involvement so that policy goals can be achieved sustainably.